An introduction to contemporary remote sensing - Weng, Qihao (New York : McGraw-Hill, 2012)
This is a practical guide to remote sensing technology, providing basic knowledge intended for diverse geospatial applications. The text covers the latest developments in remote sensing and imaging science, especially those relevant to undergraduate students.
Written by an expert in the field, An Introduction to Contemporary Remote Sensing introduces the latest developments in remote sensing and imaging science. This book covers basic principles and discusses essential technologies, such as aerial photography, radar, Lidar (light detection and ranging), photogrammetry, satellites, thermal radiation, and much more. Full-color images illustrate the concepts presented, and review questions at the end of each chapter help reinforce learning. This detailed resource provides the solid foundation in remote sensing required for developing diverse geospatial applications.
The field of remote sensing -- Electromagnetic radiation principles -- Characteristics of remotely sensed data -- Aerial photo interpretation -- Photogrammetry basics -- Remote sensors -- Earth observation satellites -- Digital image analysis -- Thermal remote sensing -- Active remote sensing.
Includes bibliographical references and index.
Keywords: Remote sensing; Geographic information systems; Fernerkundung; Fernerkundung